Sustainable Diplomacy : Expanding the Potential of Diplomatic Relations (Lessons from the Netherlands) - Dostal, Pavel (2016)
Within its scope, the thesis theoretically underpins the concept of sustainable diplomacy, using an evolutionary approach to diplomacy, and introduces criteria that allow its application on exemplary Dutch foreign policy projects. Three Dutch sustainable diplomacy projects are analyzed using a unified framework to allow their comparison and evaluation based on the criteria from the theoretical part. In light of the findings of the analysis, the thesis also acknowledges limitations of sustainable diplomacy encountered during the research to provide foundations for future development of the concept.